ACP 2019
DOI: 10.5709/acp-0268-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Binaural and Monoaural Beat Stimulation on Cognitive Functioning in Subjects with Different Levels of Emotionality

Abstract: Today, binaural and monaural beats are offered over the Internet or by mental health institutes to improve wellbeing or cognitive functioning. This improvement is explained by the assumption that the brain adapts its brainwave frequency to the frequency of the auditory beat. The present study examined the effects of binaural and monaural beat stimulation on attention and working memory in high and low emotional participants. A group of 24 participants (16 females, 8 males) between 19 and 31 years old (M = 22.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
2
18
1
Order By: Relevance
“…Application of 40 Hz gamma BB and MB for the assessment of attention (Flanker task) and working memory (Klingberg task) in high and low emotional participants showed that listening to BB at beta (15 Hz) range during the N-back task altered network connections and resulted in improvement of the accuracy of performance (Beauchene et al 2017). Another study found that both BB and MB similarly enhanced the speed of performance in the attention task and their effects were also similar in high and low emotional participants (Engelbregt et al 2019). In a study on the attentional blink (AB) using MEG recordings, it was shown that gamma (40-Hz) BB stimulation during training enhanced the attentional blink task outcomes.…”
Section: The Cognitive Effects Of Binaural Beatsmentioning
confidence: 88%
“…Application of 40 Hz gamma BB and MB for the assessment of attention (Flanker task) and working memory (Klingberg task) in high and low emotional participants showed that listening to BB at beta (15 Hz) range during the N-back task altered network connections and resulted in improvement of the accuracy of performance (Beauchene et al 2017). Another study found that both BB and MB similarly enhanced the speed of performance in the attention task and their effects were also similar in high and low emotional participants (Engelbregt et al 2019). In a study on the attentional blink (AB) using MEG recordings, it was shown that gamma (40-Hz) BB stimulation during training enhanced the attentional blink task outcomes.…”
Section: The Cognitive Effects Of Binaural Beatsmentioning
confidence: 88%
“…This may open perspectives for the treatment of pathological memory processes in addiction, including digital addiction . In addition, there is now growing evidence that binaural-beat exposure may be a choice for minimally invasive, effective therapy of anxiety syndromes and sleep disorders [ 168 , 169 , 170 ], including those associated with internet addiction disorder [ 171 , 172 ]. The therapy can be administered without prior training and consists of presenting two tones with different sound frequencies separately but simultaneously to each ear.…”
Section: Perspectives For Clinical Research and Treatmentmentioning
confidence: 99%
“…Many teams have used white noise, pink noise or blank tape as control groups in their studies and found no significant differences in the experimental results produced by these control groups [8,10,[39][40][41][42]. The results of the significance analysis of the scores of the evaluation indexes of different noises by Wu et al showed that there was no significant difference between the subjective evaluation scores of pink noise and white noise.…”
Section: B Stimulimentioning
confidence: 99%
“…Several studies have confirmed that BB have a range of effects on behavior and cognition. For example, Le Scouarnec, Brady [5] and Steven et al suggest that delta and theta band frequencies BB can reduce anxiety, promote deep meditation and increase hypnotic susceptibility; Lane [6] et al demonstrated that beta BB helped increase alertness as well as improve mood; Carlo Lovati's team demonstrated that theta and alpha BB improved migraines [7]; Gerardo Gálvez et al applied 14 Hz BB in a double-blind randomized controlled study in patients with Parkinson's disease (PD) and showed that beta-band frequencies BB can effectively affect brain activity and improve cognitive performance in Parkinson's patients [8]; In addition, previous work in children with attention deficit and hyperactivity disorder (ADHD) has shown that beta BB can also be used in brainwave induction therapy for ADHD and has a facilitative effect on the behavioral performance of children with ADHD [9]; Hessel Engelbregt et al examined the effects of 40 Hz BB and monaural beats (MB) stimulation on attention and working memory in high and low mood participants and found that participants' reaction times were faster when receiving 40 Hz BB, possibly due to the increased speed of attentional processing by gamma-frequency BB [10].…”
Section: Introductionmentioning
confidence: 99%